Pengembangan Perangkat Pembelajaran Kosakata Bahasa Inggris Berbasis Role Playing Pada Siswa SMP di Kota Makassar - Munir Munir; Ahmad Talib; Abdullah Abdullah (Seminar Nasional LP2M UNM, 2019)
Abstract. The problem statement of this research is how to develop instructional tools of teaching model and material design of Basic English vocabulary based on Role Plying for Junior High School in Makassar. This research is an extensive process to investigate students’ needs and then develop a product which is specifically design to fulfill them . This research is development research at aimed at developing instructional model and material design of basic English vocabulary based on Role Plying for SMP students in Makassar. The development of instructional design followed model of research design and development by Borg & Gall (1983). This research is an extensive process to investigate students’ needs. Subject of this research are experts of English and learning material, teacher of English and students of SMPN 2 Makassar. The result of the research showed that the development of instructional material design of basic English vocabulary for SMP students were composed well and can be used in teaching and learning process in the class room Keywords: develop instructional tools , teaching model and material design, Basic English vocabulary , Role Plying